Expression of isocitrate dehydrogenase-1 in glioblastoma, Bangladesh perspective - Mir, Ratim; Islam, M. A.; Islam, Nowfel; Islam, M. Nasimul; Das, Reba; Kabir, Enamul (International Journal of Research in Medical Sciences, 2023)
Background: Glioblastoma is the most frequent malignant brain tumor in adults. Various studies have identified IDH (isocitrate dehydrogenase) mutation as a hallmark genetic alteration in glial tumors. The World Health Organization (WHO) has classified glioblastoma based on IDH mutation status, including IDH-mutant glioblastoma, IDH-wildtype glioblastoma along with its variants and glioblastoma, NOS (not otherwise specified) (where IDH mutation status cannot be evaluated). Methods: It was a cross-sectional observational study, conducted on 35 histologically diagnosed cases of glioblastoma, within the period of March, 2018 to December 2019. Results: Among the 35 glioblastoma cases, 6 (17.14%) were found to be IDH-mutant (positive for IDH1 immunostain), while the remaining 29 cases were negative for IDH1 immunostain (therefore designated as IDH-wildtype glioblastoma). In the IDH-mutant group, 3 out of 6 patients were in the younger age group (≤40 years). On the other hand, IDH-wildtype glioblastoma was more common in elderly and most frequent was in the age group of 51-60 years (11 out of 29 cases). Conclusions: In this study, IDH1 expression was observed in 17.14% of all glioblastoma cases (designated as IDH-mutant glioblastoma). Whereas, most (~82.86%) of the glioblastoma cases did not express IDH1 (designated as IDH-wildtype).